Education as dialogue: Its prerequisites and its enemies (Author: T. Kazepides) - Marina Schwimmer, Reviewed by: (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
Tasos Kazepides. Education as dialogue: Its prerequisites and its enemies. Montreal, QC & Kingston, ON: McGill-Queen's University Press (2010). 207 pp. CDN$ 29.95 (paperback). (ISBN-13: 978-0773538061).